Preliminary Study by Differential Scanning Calorimetric Analysis of Red Blood Cells in Peripheral Artery Disease Patients Treated with Cilostazol: Correlation with Improvements in Walking Distance - Dénes Lőrinczy; Dorottya Szabó; László Benkő (Pharmaceuticals)
Objective: Peripheral artery disease (PAD) is a prevalent vascular condition characterized by arterial narrowing, which impairs blood flow and manifests as intermittent claudication, a pain or cramping sensation induced by physical activity or ambulation. Walking distance is a crucial clinical indicator of peripheral artery disease, and it correlates with the disease severity and risk of mortality. It reflects the severity of the disease, with reduced mobility indicating an increased risk of morbidity. It can also inform on the efficacy of the treatment. Cilostazol, a phosphodiesterase III inhibitor, has been demonstrated to enhance walking distance in patients with peripheral artery disease through the dilation of blood vessels and the inhibition of platelet aggregation. With this preliminary study, we aimed to elucidate other possible effects of cilostazol, specifically its influence on the structural properties of red blood cells. Methods: 10 patients (5 men, 5 women) with PAD were treated with cilostazol over a three-month period. Its biochemical effects on RBCs were determined using differential scanning calorimetry (DSC). Patient’s blood samples were collected at the start of treatment, then after two weeks, one month, two months, and three months of therapy. Results: The DSC analysis revealed shifts in thermal properties, including change in peak (melting or denaturation) temperature (Tp) and calorimetric enthalpy (ΔHcal), which indicate significant structural changes in red blood cells. These thermal property changes correlated with clinical improvements in walking distance reported by patients. Conclusions: Our findings suggest that cilostazol induces substantial biochemical modifications in red blood cells, enhancing their functional properties and contributing to improved clinical outcomes. This study highlights the potential of differential scanning calorimetry as an adjunctive method for assessing the effectiveness of treatments for peripheral artery disease at the cellular level. However, further investigation with larger patient cohorts is required to confirm these initial results.